SLU Aqua National coastal bottom trawl survey of fish along the Swedish west coast - Data curator (Swedish University of Agricultural Sciences, 2026)
Yearly monitoring programme of marine benthic fish communities along the Swedish west coast from 2002-2024 and ongoing. Since year 2013 a 16 mm mesh sized bottom trawl is used, prior to 2013 a 70 mm mesh size was used. Fish are identified to species, and their total weight and a subsample of lengths of each species are measured and recorded. Total weight of a selection of crustaceans and cephalopods species are also recorded. Sampling is carried out in quarter three. The monitoring programme is financed by the Swedish Agency for Marine and Water Management.

Monitoring is performed by the Department of Aquatic Resources, Swedish University of Agricultural Sciences (SLU). Data is stored in the database FD2 by SLU. https://www.slu.se/om-slu/organisation/institutioner/akvatiska-resurser/databaser/databasen-for-fiske-i-havet/
Keywords: Samplingevent; Samplingevent; SAMPLING_EVENT; Biological Sciences; Biologi